OUTCOME OF CLOSED REDUCTION AND CASTING IN DISPLACED SUPRACONDYLAR FRACTURE OF HUMERUS IN CHILDREN - Shoaib, Mohammad; Hussain, Amjad; Kamran, Haider; Ali, Johar (Journal of Ayub Medical College Abbottabad, 2003)
Background: Supracondylar fracture of humerus in children is most common in first decade of life and needs proper management to prevent complications like cubitus varus, elbow stiffness and compartment syndrome. There are various treatment modalities i.e. traction, closed reduction and casting, open reduction and internal fixation and percutaneous pinning. Purpose of the study was to know the outcome of closed reduction and casting in displaced supracondylar fracture of humerus in children while comparing the results with published literature. Methods: Study was conducted at the Orthopaedics unit of Lady Reading Hospital Peshawar from January 2002 to December 2002 and 25 patients at random, with age range of 04 - 12 years with displaced supracondylar fracture of humerus were treated with closed reduction and casting. Results: Based on assessment through Flynn’s criteria, results were excellent in 04 patients (16 %), good in 11 (44 %), fair in 03 (12 %) and poor in 07 patients (28 %). Conclusion: Good results can be obtained in displaced supracondylar fracture Gartland type II of humerus in children with closed reduction and casting while the results with Gartland type III fracture were not satisfactory. Keywords: Supracondylar fractures, humerus, Closed reduction